Fluorescent nanodiamonds embedded in biocompatible translucent shells - Rehor, Ivan; Slegerova, Jitka; Kucka, Jan; Proks, Vladimir; Petrakova, Vladimira; Adam, Marie-Pierre; Treussart, François; Turner, Stuart; Bals, Sara; Sacha, Pavel; Ledvina, Miroslav; Wen, Amy M; et al. (Small (Weinheim an der Bergstrasse, Germany), 2014)
High pressure high temperature (HPHT) nanodiamonds (NDs) represent extremely promising materials for construction of fluorescent nanoprobes and nanosensors. However, some properties of bare NDs limit their direct use in these applications: they precipitate in biological solutions, only a limited set of bio-orthogonal conjugation techniques is available and the accessible material is greatly polydisperse in shape. In this work, we encapsulate bright 30-nm fluorescent nanodiamonds (FNDs) in 10-20-nm thick translucent (i.e., not altering FND fluorescence) silica shells, yielding monodisperse near-spherical particles of mean diameter 66 nm. High yield modification of the shells with PEG chains stabilizes the particles in ionic solutions, making them applicable in biological environments. We further modify the opposite ends of PEG chains with fluorescent dyes or vectoring peptide using click chemistry. High conversion of this bio-orthogonal coupling yielded circa 2000 dye or peptide molecules on a single FND. We demonstrate the superior properties of these particles by in vitro interaction with human prostate cancer cells: while bare nanodiamonds strongly aggregate in the buffer and adsorb onto the cell membrane, the shell encapsulated NDs do not adsorb nonspecifically and they penetrate inside the cells.
Keywords: fluorescenční barviva; Biocompatible Materials; nádorové buněčné linie; oxid křemičitý; Electrons; nanodiamanty; Fluorescent Dyes; luminiscence; Spectrophotometry, Infrared; Microscopy, Confocal; biokompatibilní materiály; Cell Line, Tumor; Polyethylene Glycols; Luminescence; konfokální mikroskopie; polyethylenglykoly; nanoparticles; Humans; Silicon Dioxide; biocompatibilization; fluorescent nanodiamonds; elektrony; spektrofotometrie infračervená; Nanodiamonds; lidé